Analisa Pengaruh Gaya Kepemimpinan Dan Latar Belakang Pendidikan Mandor Terhadap Kinerja Tukang Dan Pekerja Pada Proyek Rumah Sakit Ubaya Surabaya - Sovi Romadyna,; Muslimatul Mufida,; Aulia Rahman O,; Hariyono Seputro Y.P., (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
The benchmark for the success of a construction project is determined by several factors. One of these factors is the resources available or involved in the project. "The resources available as input consist of the 5 Ms: Man (human/labor), Machine (tools used), Material (materials used), Money (capital), and Managerial (methods used). These improvement efforts must be based on an appropriate vision, mission, and strategy. Therefore, monitoring the foreman's performance is crucial. Based on the explanation above, the researcher will discuss here the influence of the foreman's leadership style and educational background on the performance of the craftsmen and workers on the Ubaya Hospital Surabaya project - PT Mukti Adhi Sejahtera